'The doing is everything': a middle-voiced reading of agency in Nietzsche. Issue 1 (2nd January 2020) - Han-Pile, Béatrice
ABSTRACT: Nietzsche's famous claim, 'das Thun ist Alles', is usually translated as 'the deed is everything'. I argue that it is better rendered as 'the doing is everything'. Accordingly, I propose a processual reading of agency in GM 1 13 which draws both on Nietzsche's reflections on grammar, and on the Greek middle voice, to displace the opposition between deeds and events, agents and patients by introducing the notion of middle-voiced 'doings'. The relevant question then is not 'is this a doing or a happening?' but 'what is the process unfolding in the doer, and what is her engagement with it?'. I argue (a) that this middle voiced reading makes better sense than either naturalist or expressivist interpretations of the key thought in GM 1 13 that 'there is no doer behind the doing', and (b) that GM 1 13 does not only provide us with a critique of slave morality, as is often said, but also with an example of a middle-voiced doing: self-deception. I explore the phenomenology of middle-voiced doings in other passages and show that it has at least three features: (pre-)reflective awareness of being engaged with an internal process, responsiveness, and absence of reflective control.